Uma andorinha sozinha não faz verão: o processo de participação social em Projetos de Intervenção Urbana (PIU) na cidade de São Paulo - Mendes, Andresa Cazarine (2019)
The present work is the result of a research carried out in the context of the participatory process of the municipal urban planning policy of the city of São Paulo called PIU - Urban Intervention Project - which was established by Decree No. 56,901, March 29, 2016. The research takes as object of study the peculiarity of one of the thirteen PIUs that are in progress in the city, the Arco Jurubatuba PIU. Based on the theoretical and methodological conceptions of Socio-Historical Psychology and in studies by Vygotsky about thought and language, the research has as general objective to characterize the phenomenon of social participation in an urban policy of the city of São Paulo, presenting two specific objectives: 1) identify which are the senses/meanings attributed to the phenomenon of social participation by its participants and 2) present and characterize instruments of social control, such as public consultation and public hearing. The empirical research was developed from three main procedures: a) consultation and analysis of specific documents of the Arco Jurubatuba PIU; b) monitoring public hearings and c) holding individual interviews with four participants in public hearings, residents of the region named Arco Jurubatuba. The analyzes referring to procedure a) showed that there was not a single comment in the public consultations carried out by residents or leaders of the communities of the Arco Jurubatuba region. On the other hand, for the stage of the public hearings, procedure b), there was no call for communities and community leaders, being this public participation possible through public defenders who informed the community leaders of the region, who in turn called the residents. Finally, from the narratives of the participants, developed in procedure c) five categories of analysis were defined: 1) The arrival of Jurubatuba Arco PIU; 2) The participation in the public hearings; 3) The role of community leadership and NGOs; 4) Why fight? Why participate? and 5) The struggle for survival - suffering. The participants of this research, through their narratives, presented new senses/meanings for the phenomenon of social participation. It is through social participation that they denounce the social inequality to which they are exposed daily, that they claim their rights and maintain the struggle for living dwelling. Social participation in this context assumes the purpose of combating social exclusion